Analisis Fasilitas Yang Digunakan Dalam Proses Pelayanan Informasi Aeronautika Di PIA Wilayah Denpasar - Hanifah Agisya, Binda Husnun Hanifah Agisya; Amir, Elfi; Wagini, Dini (Jurnal Bisnis dan Operasi Penerbangan, 2025)
Aeronautical Information Services (AIS) is a service responsible for ensuring the safety, regulation, and efficient air navigation through providing information and data related to aviation. Aeronautical Information Services (AIS) is a service established within a specific geographical area responsible for providing flight information and data. Therefore, it requires supporting facilities to provide high-quality information to support airline operations. In this journal, a qualitative approach with descriptive data is employed. Data collection is done through direct observation (direct observation) as an insider directly conducts On-the-Job Training at the AIS in the Denpasar Region.